Synthesis of Nano Zinc Oxide Heterogeneous Catalyst Supported with Fly Ash (NZO/FA) for Kapok Seed Oil (Ceiba pentandra) Transesterification - Asri, Nyoman Puspa; Siswoyo, Deddy Kurniawan Putra; Somadiharja, Yohannes (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2023)
A biodiesel product was developed using the transesterification of kapok seed oil using a nano zinc oxide heterogeneous catalyst with fly ash buffer (NZO/FA) to support the goal of adopting biofuel as a national transportation energy source in 2050. Because it is affordable, environmentally benign, and has a high porosity level, fly ash was selected as a catalyst buffer. Kapok seed oil, on the other hand, is employed as a raw material because of its high oil content—between 25 and 40 percent—and because it offers the best means of resolving the problem of the trade-off between food and fuel in the energy and pagan sectors. In this study, the NZO/FA 50-Sto catalyst's characterisation in the creation of heterogeneous catalysts and the impact of varying transesterification times on biodiesel yield are the main research topics. The NZO/FA-TO-4.5H sample code produced at a calcination temperature of 500°C for 5 hours with a yield percentage of 95.93%, transesterification time of 4.5 hours, oil to methanol molar ratio of 1:15, and transesterification reaction temperature of 80°C was found to have the highest yield in this study. Meanwhile, SNI 7182: 2015's standards are almost entirely met by the biodiesel produced in general terms.